Asymmetric Neutrality Regulation and Innovation at the Edges: Fixed vs. Mobile Networks - Jay Pil Choi; Doh-Shin Jeon; Byung-Cheol Kim (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study how net neutrality regulations affect a high-bandwidth content provider's (CP) investment incentives in quality of services (QoS). We find that the effects crucially depend on network capacity levels. With limited capacity, as in mobile networks, prioritized delivery services are complementary to the CP's investments and can facilitate entry of congestion-sensitive content; however, this creates more congestion for other existing content. By contrast, if capacity is relatively large, as in fixed-line networks, prioritized services reduce QoS investment as they become substitutes, but improves traffic management. These results are qualitatively robust to the extension of the ISP's endogenous choice of network capacity.
Keywords: D40; K20; L10; L50; O30; 330; net neutrality; asymmetric regulation; quality of service; investment incentives; queuing; congestion; mobile/fixed networks